Assessment of treatment adherence among hypertensive patients in a coastal area of Karnataka, India - Mallya, Sneha D.; Kumar, Ashwini; Kamath, Asha; Shetty, Avinash; Reddy T., Sravan K.; Mishra, Surabhi (International Journal Of Community Medicine And Public Health, 2017)
Background: Hypertension is the most prevalent non communicable disease. With the rising burden of hypertension, prevention of complications such as cardiovascular events or stroke resulting due to uncontrolled blood pressure is of paramount significance. Strict adherence to prescribed antihypertensive medications is the key to blood pressure control and prevention of its complications and mortality. Hence, the present study was conducted with the objective of assessing the medication adherence among hypertensive patients on treatment. Methods: A community based cross sectional study was conducted among 200 hypertensive patients on treatment for at least a year. Results: The study included 200 hypertensive patients on medication, 69% of them being females. More than two third (79.5%) were literate and 37% of study population were classified as under below poverty line. Most (39.5%) of the patients were 60-69 years of age and 55% of the patients were on treatment for over 5years. Majority (96%) of the hypertensive subjects in the study population were having an adherence rate of ≥85%. About 13% of the individuals had an interrupted treatment in the last one month. The most common reasons for missing the medications were being forgetful and not having any symptoms. Conclusions: The adherence rate in the current study is high, this needs to be maintained and further optimised.